PENGGUNAAN VIDEO ANIMASI UNTUK MENINGKATKAN MINAT DAN HASIL BELAJAR BAHASA INDONESIA SISWA KELAS V - Silvia, Claudia; Sumarni, Margaretha Lydia; Kusnanto, Kusnanto (FKIP Universitas Wisnuwardhana, 2025)
This research seeks to enhance the engagement and educational results in Indonesian language for fifth grade pupils by utilizing animated videos as a teaching tool. The foundation of this research is rooted in the low student engagement and poor performance in Indonesian language classes, which have not achieved the Minimum Mastery Criteria (MMC). This problem arises from repetitive teaching techniques and the absence of stimulating, interactive resources in education. The research utilized a Classroom Action Research (CAR) methodology carried out in two phases. Every cycle included stages of planning, executing, observing, and reflecting. The study participants were fifth graders at a public elementary school. Data were gathered utilizing observations of student learning activities, questionnaires on learning interest, and tests of academic achievement. The findings revealed that incorporating animated videos greatly heightened students' interest, as demonstrated by their lively involvement, excitement, and engagement throughout the lessons. Furthermore, students' academic results enhanced in every cycle. Consequently, animated video content has shown to be effective in improving both engagement and educational results in Indonesian language for fifth graders, acting as an appealing and pertinent option to meet the learning requirements of modern students.